Training On Making Learning Videos For High School Students To Improve Critical Thinking Skills - Erikson Simbolon; Paulinus Tibo; Paulus Halek Bere; Petrus Simarmata; Rolando Sipayung; Mila Angraini Sinuhaji; Hot Uli Sitanggang (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Critical thinking is an important skill that students must possess in order to objectively analyze learning issues and make decisions about learning. Critical thinking can be enhanced through the creation of educational videos relevant to Catholic religious education. The goal of this training is to conduct a workshop on creating educational videos for students to improve their critical thinking skills. To achieve this training goal, the community service program involving faculty and students is designed in five sessions:1. Training socialization.2. Explaining the concept of improving critical thinking skills through training on creating educational videos.3. Training on creating educational videos. 4. Practice creating Catholic Religious Education (PAK) instructional videos. 5. Evaluation of the training implementation to assess the students' knowledge development. The training on the creation of educational videos includes the collection of feedback from the participants on the video creation process in order to improve the critical thinking skills of the students. The goal of this training is for students to be able to create educational videos that enhance their critical thinking skills. The impact of this training is that students will gain knowledge about creating educational videos and show an improvement in critical thinking skills in the process of creating engaging videos that are consistent with the characteristics of PAK learning.